2004
DOI: 10.1016/s1090-3801(03)00074-0
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of pain problems and depressive symptoms in young women: results from a cross‐sectional survey among women aged 15–24 in Hungary

Abstract: Frequent headaches and musculoskeletal pain problems were assessed as part of a cross-sectional health survey in a representative sample of 3615 young Hungarian women, aged 15-24 (mean age: 19.0 years). The representative sample was obtained by a multilevel stratified sampling procedure based on national statistical data, the refusal rate was 6%. Depressive symptomatology was assessed as well using the shortened form of the Beck Depression Inventory. The overall prevalence of frequent headaches was 43.8% in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
3
11
1
Order By: Relevance
“…In contrast to previous research, 42,53 our findings did not reveal significant associations among depression status and chronic pain. While the PHQ-2 is a validated screening measure for depression, it does not provide a comprehensive assesment of depressive symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous research, 42,53 our findings did not reveal significant associations among depression status and chronic pain. While the PHQ-2 is a validated screening measure for depression, it does not provide a comprehensive assesment of depressive symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…The Functional Disability Index (FDI) 13, 33 is a 15-item scale where patients report their perceptions of how much physical trouble and difficulty they have had performing daily activities in the past two weeks. A total score is computed by summing all the items.…”
Section: Methodsmentioning
confidence: 99%
“…A cross-sectional health survey of 3615 young Hungarian women, aged 15-24, showed that frequent headaches were experienced by 43.8% of the sample, while 25.8% reported chronic musculoskeletal pain (Rethelyi et al, 2004). The presence of depression was significantly higher in subjects reporting pain with 11.2% occurrence of depression in the group with frequent headaches and 10.3% occurrence in the group with musculoskeletal pain.…”
Section: Co-occurrence Of Pain and Depressionmentioning
confidence: 99%